Using intervention mapping to develop a theory-driven, group-based complex intervention to support self-management of osteoarthritis and low back pain (SOLAS). (December 2015) - Hurley, Deirdre; Murphy, Laura; Hayes, David; Hall, Amanda; Toomey, Elaine; McDonough, Suzanne; Lonsdale, Chris; Walsh, Nicola; Guerin, Suzanne; Matthews, James
Abstract Background The Medical Research Council framework provides a useful general approach to designing and evaluating complex interventions, but does not provide detailed guidance on how to do this and there is little evidence of how this framework is applied in practice. This study describes the use of intervention mapping (IM) in the design of a theory-driven, group-based complex intervention to support self-management (SM) of patients with osteoarthritis (OA) and chronic low back pain (CLBP) in Ireland's primary care health system. Methods The six steps of the IM protocol were systematically applied to develop the self-management of osteoarthritis and low back pain through activity and skills (SOLAS) intervention through adaptation of the Facilitating Activity and Self-management in Arthritis (FASA) intervention. A needs assessment including literature reviews, interviews with patients and physiotherapists and resource evaluation was completed to identify the programme goals, determinants of SM behaviour, consolidated definition of SM and required adaptations to FASA to meet health service and patient needs and the evidence. The resultant SOLAS intervention behavioural outcomes, performance and change objectives were specified and practical application methods selected, followed by organised programme, adoption, implementation and evaluation plans underpinned by behaviour change theory. Results The SOLAS intervention consists of six weekly sessions of 90-min education and exercise designed to increase participants' physical activity level and use of evidence-based SM strategies (i.e. pain self-management, pain coping, healthy eating for weight management and specific exercise) through targeting of individual determinants of SM behaviour (knowledge, skills, self-efficacy, fear, catastrophizing, motivation, behavioural regulation), delivered by a trained physiotherapist to groups of up to eight individuals using a needs supportive interpersonal style based on self-determination theory. Strategies to support SOLAS intervention adoption and implementation included a consensus building workshop with physiotherapy stakeholders, development of a physiotherapist training programme and a pilot trial with physiotherapist and patient feedback. Conclusions The SOLAS intervention is currently being evaluated in a cluster randomised controlled feasibility trial. IM is a time-intensive collaborative process, but the range of methods and resultant high level of transparency is invaluable and allows replication by future complex intervention and trial developers.